A dual-site two-photon fluorescent probe for visualizing lysosomes and tracking lysosomal hydrogen sulfide with two different sets of fluorescence signals in the living cells and mouse liver tissues. Issue 43 (9th May 2016) - Liu, Yong; Meng, Fangfang; He, Longwei; Liu, Keyin; Lin, Weiying
Abstract : We have firstly developed a fluorescent probeTP-PMVC, which can monitor lysosomes and lysosomal H2 S with dual signal. Abstract : Herein, we have developed a novel dual-site two-photon fluorescent probeTP-PMVC as the first paradigm of the probes, which can concurrently report lysosomes and lysosomal H2 S with two different sets of fluorescence signals in the living cells and tissues.